(3eaghe GdeHGOQI (B- (3GSJQGJjLjI GdeHGOQI (B- (3JMdjd GdaQU GdeMdjI hGdOhdjI s - (3YdGA(B, (3YHGSs ((3GdEScfOQjI(B:s (3OGQ GdJYdje GdLGeYj(B,s)
(3JfGhd gPG GdcJGH ehVhY QjGOI GdCYeGd hGdeTQhYGJ GdUZjQI ef NdGd GdJWQb Gddi eaghe hGSJQGJjLjI GdeHGOQI hWQjbI JacjQ GdeHGOQ , HGdGVGaI Gdi JMOjO hJMdjd GdaQU GdeMdjI hGdOhdjI s
Keywords: (3EOGQI GdCYeGds; (3GdeTQhYGJs